Mild hyperthermia with magnetic resonance- guided high intensity focused ultrasound combined with salvage chemoradiation for recurrent rectal cancer - Jonathan Peng; Ari Partanen; Samuel Pichardo; Robert Staruch; Kaitlyn Perry; Merrylee McGuffin; Yuexi Huang; Kelvin KW. Chan; Shun Wong; Greg Czarnota; Kullervo Hynynen; William Chu (International Journal of Hyperthermia)
Introduction Pelvic recurrences from rectal cancer present a challenging clinical scenario. Hyperthermia represents an innovative treatment option in combination with concurrent chemoradiation to enhance therapeutic effect. We provide the initial results of a prospective single center feasibility study (NCT02528175) for patients undergoing rectal cancer retreatment using concurrent chemoradiation and mild hyperthermia with MR-guided high intensity focused ultrasound (MR-HIFU).Methods All patients were deemed ineligible for salvage surgery and were evaluated in a multidisciplinary fashion with a surgical oncologist, radiation oncologist and medical oncologist. Radiation was delivered to a dose of 30.6 Gy in 1.8 Gy per fraction with concurrent capecitabine. MR-HIFU was delivered on days 1, 8 and 15 of concurrent chemoradiation. Our primary objective was feasibility and toxicity.Results Six patients (total 11 screened) were treated with concurrent chemoradiation and mild hyperthermia with MR-HIFU. Tumor size varied between 3.1-16.6 cm. Patients spent an average of 228 min in the MRI suite and sonication with the external transducer lasted an average of 35 min. There were no complications on the day of the MR-HIFU procedure and all acute toxicities (no grade >/=3 toxicities) resolved after completion of treatment. There were no late grade >/=3 toxicities.Conclusion Mild hyperthermia with MR-HIFU, in combination with concurrent chemoradiation for appropriately selected patients, is safe for localized pelvic recurrences from rectal cancer. The potential for MR-HIFU to be applied in the recurrent setting in rectal cancer treatment requires further technical development and prospective evaluation.